PENGARUH AKUNTABILITAS, KEPUASAN KERJA, BATASAN WAKTU PEMERIKSAAN DAN KONFLIK PERAN TERHADAP KINERJA PEMERIKSA PAJAK KPP PRATAMA DAN MADYA PEKANBARU - Muhammad Iqbal Ridwan; Zirman '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The research aims to examine the effect of accountability, work satisfaction, audit time deadline and role conflict to the tax auditors performance at tax office of Pekanbaru. The data in this study is the primary data. The population in this study were the tax auditors who worked in the tax office of Pekanbaru. The sampling method used in this study saturated sampling method. The sample used in this study were 56 respondents. The method of data analysis used to the test the hypotesis is multiple regression analysis by using SPSS 21 version.The results of this study is showed that accountability, work satisfaction, audit time deadline influence on the tax auditors performance. The magnitude of the effect caused by Adjusted R² by four variables is 43,3% of the dependent variable, while the remaining 56,7% is influenced by other independent variabel that are not observed in this study.Keywords : Accountability, Work Satisfaction, Audit, Role, and Performance